A comparative analysis of Pseudophase Ion-Exchange (PIE) model and Berezin Pseudophase (BPP) model: analysis of kinetic data for Ionic Micellar-Mediated Semi-Ionic Bimolecular Reaction - Ariffin, Azhar; Khan, M.N.; Cheong, M.Y. (2007)
Pseudo-first-order rate constants (k(obs)) for the reaction of N-benzylphthalimide (NBPT) with HO- have been determined at 2.0 x 10(-4) M NBPT, 1.0 x 10(-3) and 2.0 x 10(-3) M NaOH as well as varying concentrations of cetyltrimethylammonium bromide ([CTABr](T) = 0.0-1.7 x 10(-1) M). The effects of [CTABr](T) - CMC (with CMC representing the critical micelle concentration of CTABr) on k(obs) have been analyzed in terms of Berezin's pseudophase (BPP) model and pseudophase ion-exchange (PIE) model. Although both models give the best observed data fit with least-squares values not significantly different from each other, the calculated values of K-S from BPP model appear to be more reliable compared to those from PIE model because the values of K-S from BPP model are similar to the corresponding K-S values determined spectrophotometrically.